The compatibility of rhenium and osmium in natural olivine and their behaviour during mantle melting and basalt genesis - Burton, K; Gannoun, A; Birck, J; Allegre, C; Schiano, P; Clocchiatti, R; Alard, O (2002)
Rhenium and osmium (Re-Os) elemental abundances have been obtained for magmatic olivine from a range of host basalt compositions, for mantle olivine and coexisting phases (silicate and sulphide) from a spinel-peridotite, and olivine and Fe-Ni metal from Pallasite meteorites. These data indicate that Re and Os concentrations in olivine are low in both mantle and magmatic environments, and both elements preferentially partition into silicate melt, sulphide or Fe-Ni metal, relative to olivine. For magmatic olivine the partition coefficients for Re and Os correlate with the MgO content of the olivine (like Fe, Mn and Ni), which suggests that the observed partitioning reflects substitution onto crystallographic sites, rather than defects or the presence of included phases. These data indicate that Os is extremely incompatible (that is, excluded from the silicate structure) in magmatic olivine, which suggests that olivine crystallisation alone cannot be responsible for the low Os contents of some oceanic basalts. Rather, olivine crystallisation is itself responsible for sulphide precipitation (in which Os is highly compatible), by producing sulphur saturation of the melt, and it is the coupled crystallisation of these phases that effects the Os-Mg-Ni co-variations observed in oceanic basalts. Rhenium is also incompatible in magmatic olivine but the data suggest that for Fe-rich olivine compositions Re may become compatible, which may explain, at least in part, the compatible behaviour of this element during basalt petrogenesis on other planetary bodies, such as Mars and the Moon. Preliminary data for mantle olivine, not demonstrably contaminated by included phases, suggest that the high Os concentrations (relative to magmatic olivine) relate to partitioning with a sulphide, rather than silicate melt. © 2002 Elsevier Science B.V. All rights reserved.